2012
DOI: 10.1002/adfm.201103152
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Oxide as an Olefin Polymerization Carbocatalyst: Applications in Electrochemical Double Layer Capacitors

Abstract: Graphite oxide (GO) is shown to be an effi cient heterogeneous catalyst for the polymerization of various olefi n monomers, including n-butyl vinyl ether, N -vinylcarbazole, styrene, and sodium 4-styrenesulfonate. The GO-catalyzed polymerization of n-butyl vinyl ether (0.1-5.0 wt% GO relative to monomer) proceeds rapidly under solvent-free conditions and affords polymers with moderate number average molecular weights and broad polydispersities. Analysis of the carbon recovered at the conclusion of the polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 65 publications
5
47
0
Order By: Relevance
“…Furthermore, when the same experiment was performed with GO as the catalyst, 19 % styrene conversion was observed, although the products did not result from oxidation, but the di‐ and oligomerization of styrene, as evidenced by GC‐MS analysis. Recent precedents reported in the literature by Bielawski and co‐workers are in agreement with this catalytic activity of GO, because these authors have shown the remarkable ability of GO to promote styrene oligo‐ and polymerization 4345. In contrast to these results, an analogous sample of GO obtained by the same procedure had been found previously to act as a carbocatalyst for the aerobic oxidation of benzyl alcohol,24 although much larger amounts were employed than in the reaction here.…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, when the same experiment was performed with GO as the catalyst, 19 % styrene conversion was observed, although the products did not result from oxidation, but the di‐ and oligomerization of styrene, as evidenced by GC‐MS analysis. Recent precedents reported in the literature by Bielawski and co‐workers are in agreement with this catalytic activity of GO, because these authors have shown the remarkable ability of GO to promote styrene oligo‐ and polymerization 4345. In contrast to these results, an analogous sample of GO obtained by the same procedure had been found previously to act as a carbocatalyst for the aerobic oxidation of benzyl alcohol,24 although much larger amounts were employed than in the reaction here.…”
Section: Resultssupporting
confidence: 89%
“…This phenomenon has drawn considerable attention because of its crucial role in the carbon19 and iron20 cycles. GO is transparent and functions as a solid state Lewis acid (p K a  = 3–4) in water because of its carboxyl groups21222324. Thus, the photochemical behavior of the material combining GO with Fe 3+ in aqueous environment is particularly interesting and has not been studied yet.…”
mentioning
confidence: 99%
“…4,5 Modification of the plastic is also an option, for instance grafting maleic anhydride onto the plastic chains enhances their polarity and/or chemical reactivity toward wood cell wall polymers. 3,[6][7][8][9] Silane coupling agents may create interfacial adhesion at the surface of various phases and have been extensively used in composites. 10,11 Organofunctional silanes have a generic chemical structure, R n -Si-(R 0 X) (4-n) , where R is alkoxy, X represents an organofunctionality, and R 0 is an alkyl bridge (or alkyl spacer) connecting the silicon atom and the organofunctionality.…”
Section: Introductionmentioning
confidence: 99%